The Idea of School Education Organization on the Basis of Individualization and Differentiation in Activity of the Ussr People’s Commissariat of Education in The Early 1920s of the Twentieth Century - Berezovskaya, Larysa (Pedagogical Discourse, 2012)
Article covers organizational-conceptual characteristics of differentiation as a form of implementation of a training individualization principle in school policy of the USSR People’s Commissariat of Education in the early 1920s of the twentieth century.